2017
DOI: 10.1007/s12639-017-0954-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of amphistome infection in sheep from Mhow, Madhya Pradesh

Abstract: A total of 445 faecal samples and 128 rumens of sheep collected from Slaughter house, Mhow (Madhya Pradesh) were examined for a period of 1 year from February 2011 to January 2012. Faecal sample examination based, incidence of amphistomes was found to be 23.37% from the study area. The incidence of amphistomes was significantly higher ( < 0.01) during summer (36.75%) than winter (27.74%) and monsoon (3.52%). Age-wise, non-significantly higher infection was observed in ≥1 year-old animals (23.61%) than <1 year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…Our findings were in accordance with Bansal et al. (2018) in sheep from India and Javed Khan et al. (2008) in cattle from Pakistan.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were in accordance with Bansal et al. (2018) in sheep from India and Javed Khan et al. (2008) in cattle from Pakistan.…”
Section: Discussionsupporting
confidence: 93%
“…The rate of contamination of fresh and dry forage with amphistomum eggs and the metacercariae Significantly (p < .0001) higher infection of amphistomes was recorded during summer season (60%) followed by autumn (40%), spring (28%) and winter (10.4%). Our findings were in accordance with Bansal et al (2018) in sheep from India and Javed Khan et al (2008) in cattle from Pakistan. However, Nikpay et al (2019), Ozdal et al (2010) and Eslami et al (2011) showed that the highest infection rate of amphistomum was in spring, autumn, summer and winter respectively.…”
Section: Ta B L Esupporting
confidence: 93%